Physical effort biases the perceived pleasantness of neutral faces: A virtual reality study. (November 2022) - Cheval, Boris; Maltagliati, Silvio; Fessler, Layan; Farajzadeh, Ata; Ben Abdallah, Sarah N.; Vogt, François; Dubessy, Margaux; Lacour, Maël; Miller, Matthew W.; Sander, David; Boisgontier, Matthieu P.
Abstract: The role of affective responses to effort in the regulation of physical activity behavior is widely accepted. Yet, to investigate these affective responses during physical activity, most studies used direct self-reported measures that are prone to biases (e.g., social desirability, ability to introspect). To reduce these biases, we used an indirect measure (i.e., an affect misattribution procedure) that assessed the implicit affective valence elicited by physical effort in 42 healthy young adults. Specifically, participants rated the pleasantness of neutral human faces presented in a virtual environment while cycling at different intensities. We used this rating as an indicator of implicit affective valence. Results showed that higher perceived effort was associated with lower pleasantness ratings of neutral faces, with this effect only emerging at moderate-to-high levels of perceived effort. Further analyses showed that higher actual effort was also associated with lower pleasantness ratings of neutral faces. Overall, these findings suggest that higher levels of perceived effort are associated with decreased affective valence during physical activity. Finally, this study presents a new indirect measure of affective valence during physical activity. Highlights: Affective mechanisms are instrumental to the regulation of physical activity. We developed an indirect self-reported measure of affective valence during physical activity. In this task, participants rated the pleasantness of neutral faces at different levels of effort. Higher perceived effort was associated with lower pleasantness ratings of neutral faces. Affective responses during physical activity can be assessed using an indirect self-report measure.